Job satisfaction and attitudes toward organisational change : a study at the national school of government - Malatjie, I.; Montana, A. (IPADA, 2019)
Organisational changes happen too frequently in some organisations due to a reaction to the disruptive and turbulent environmental factors that shape the current practices of those organisations and result in changes towards their organisational values. Organisational change has become a significant part of work life, with changes impacting not only on an organisational level but also on a personal employee level. The purpose of this study is to explore the impact of organisational change on job satisfaction and attitudes of employees towards the change. Empirical research was conducted on a research sample of 229 employees of the National School of Government (NSG). A survey was administered to all employees of the NSG. A total number of 109 employees responded to the questionnaire and only 103 of these questionnaires were usable. Detailed analysis indicated that there is a strong positive statistical relation between organisational change and job satisfaction. Keywords: Job satisfaction, Organisational change, Uncertainty attitude, Strategy
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Job satisfaction; Organisational change; Uncertainty attitude; Strategy; Job satisfaction -- South Africa; Organisational change -- South Africa